Studia nad kinem a historia sztuki - Albera, François; Grąbczewska, Małgorzata (Artium Quaestiones, 2020)
Translation of François Albera's article originally published in French. The article traces the relationship between film studies and art history in its diverse manifestations and aspects throughout the 20th century.